Secondary battery and electric device

CN122907593APending Publication Date: 2026-10-13XIAMEN AMPACE TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611406826.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本公开通过使第一材料包括硬碳,12.5≤σe1/σe2≤250,10≤σe1≤50,负极膜层具有良好的电子传导性能,能降低极化,同时第一涂层具有适中的电子电导率,既能补偿负极膜层边缘位置的容量,改善负极膜层例如边缘削薄、涂布不均、正极边缘效应造成的局部容量失配,改善负极膜层边缘位置金属析出问题,还能改善二次电池的循环性能、动力学性能和使用可靠性

Benefits of technology

[0030]本公开提供了一种二次电池以及用电设备。通过使二次电池的负极极片包括负极集流体、负极膜层和第一涂层,第一涂层包括第一材料和第一粘结剂,第一材料包括硬碳,负极膜层25℃下的电子电导率为σe1S/cm,第一涂层25℃下的电子电导率为σe2S/cm,负极极片满足:12.5≤σe1/σe2≤250,其中,10≤σe1≤50,负极膜层具有良好的电子传导性能,能降低极化,同时第一涂层具有适中的电子电导率,既能补偿负极膜层边缘位置的容量,改善负极膜层例如边缘削薄、涂布不均、正极边缘效应造成的局部容量失配,改善负极膜层边缘位置金属析出问题,还能改善二次电池的循环性能、动力学性能和使用可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122907593A_ABST
    Figure CN122907593A_ABST
Patent Text Reader

Abstract

The disclosure discloses a secondary battery and a power consumption device, the secondary battery comprising a negative electrode sheet, a positive electrode sheet and a separator, the negative electrode sheet comprising a negative electrode current collector, a negative electrode film layer and a first coating layer, the negative electrode film layer being arranged in a coating area, the first coating layer being at least partially arranged in a transition area, the negative electrode active material comprising graphite, the positive electrode sheet comprising a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector, the positive projection of the first coating layer and the positive projection of the positive electrode film layer not overlapping in the thickness direction of the positive electrode sheet; the first coating layer comprising a first material and a first binder, the first material comprising hard carbon, the electronic conductivity of the negative electrode film layer at 25 DEG C being sigma e1 S / cm, the electronic conductivity of the first coating layer at 25 DEG C being sigma e2 S / cm, the negative electrode sheet satisfying: 12.5 <= sigma e1 / sigma e2 <= 250, wherein 10 <= sigma e1 <= 50.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure belongs to the field of electrochemical technology, specifically relating to a secondary battery and an electrical device. Background Technology

[0002] As the application range of rechargeable batteries becomes increasingly wide, higher requirements are being placed on their performance. Currently, during the preparation of the negative electrode sheet, the edges of the negative electrode film are thinned, resulting in reduced capacity at the edges and a higher risk of metal deposition, which affects the cycle performance and kinetic performance of the rechargeable battery. Summary of the Invention

[0003] This disclosure provides a secondary battery and an electrical device that can improve the cycle performance and kinetic performance of the secondary battery.

[0004] In a first aspect, this disclosure provides a secondary battery comprising an electrode assembly, the electrode assembly including a negative electrode, a positive electrode, and a separator, the separator being located between the negative and positive electrode. The negative electrode includes a negative current collector, a negative electrode film, and a first coating. The negative current collector includes a negative electrode body and a negative electrode tab extending from one end of the negative electrode body. The negative electrode body includes a coating region and a transition region, the transition region being disposed between the negative electrode tab and the coating region. The negative electrode film is disposed in the coating region, and the first coating is at least partially disposed in the transition region. The negative electrode film includes a negative electrode active material and a negative electrode binder, the negative electrode active material including graphite. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. Along the thickness direction of the positive electrode, the orthographic projection of the first coating does not overlap with the orthographic projection of the positive electrode film. The first coating includes a first material and a first binder, the first material including hard carbon. The electronic conductivity of the negative electrode film at 25°C is σ. e1 S / cm, the electronic conductivity of the first coating at 25°C is σ e2 S / cm, the negative electrode plate satisfies: 12.5≤σ e1 / σ e2 ≤250, where 10≤σ e1 ≤50.

[0005] This disclosure makes the first material include hard carbon, 12.5≤σ e1 / σ e2 ≤250, 10≤σ e1 With a value of ≤50, the negative electrode film has good electronic conductivity, which can reduce polarization. At the same time, the first coating has moderate electronic conductivity, which can not only compensate for the capacity at the edge of the negative electrode film, but also improve the local capacity mismatch caused by edge thinning, uneven coating, and positive electrode edge effect, and improve the metal deposition problem at the edge of the negative electrode film, but also improve the cycle performance, kinetic performance and reliability of the secondary battery.

[0006] In some embodiments, the negative electrode plate satisfies: 25 ≤ σ e1 / σ e2 ≤150.

[0007] In some embodiments, the negative electrode plate satisfies: 15 ≤ σ e1 ≤30.

[0008] In some embodiments, 0.1 ≤ σ e2 ≤1.6. This can not only compensate for the capacity at the edge of the negative electrode film, improve the local capacity mismatch of the negative electrode film, and improve the metal deposition problem at the edge of the negative electrode film, but also improve the cycle performance, kinetic performance and reliability of the secondary battery.

[0009] In some embodiments, the capacity per unit area of ​​the first coating is Q2 mAh / cm². 2 The capacity per unit area of ​​the positive electrode film is Q. p mAh / cm 2 The secondary battery satisfies: 1.05 ≤ Q² / Q p ≤1.30. This can better improve the local capacity mismatch of the negative electrode film, improve the metal deposition problem at the edge of the negative electrode film, and improve cycle performance and kinetic performance, while not affecting the energy density and initial coulombic efficiency of the secondary battery.

[0010] In some embodiments, the capacity per unit area of ​​the first coating is Q2 mAh / cm². 2 The capacity per unit area of ​​the positive electrode film is Q. p mAh / cm 2 The secondary battery satisfies: 10.4 ≤ (σ e1 / σ e2 ) / (Q2 / Q p ≤227.3. This balances the electron blocking and capacity compensation effects of the first coating, improves the metal deposition problem at the edge, and improves the cycle performance and kinetic performance of the secondary battery, without affecting the energy density and initial coulombic efficiency of the secondary battery.

[0011] In some embodiments, a first coating is provided on both surfaces of the negative electrode current collector in the thickness direction, and the two first coatings form fusion regions of different widths with the adjacent negative electrode film layers.

[0012] In some embodiments, a first coating is provided on both surfaces of the negative electrode current collector in the thickness direction, and the boundaries of the two first coatings away from the negative electrode film layer are staggered from each other along the width direction of the negative electrode current collector.

[0013] In some embodiments, a first coating is provided on both surfaces of the negative electrode current collector in the thickness direction. Along the thickness direction of the negative electrode current collector, the orthographic projections of the two first coatings parallel to the length direction of the negative electrode current collector and away from the boundary of the negative electrode film layer do not coincide.

[0014] In some embodiments, the mass percentage of the negative electrode binder, based on the total mass of the negative electrode film, is W. 11 Based on the total mass of the first coating, the mass percentage of the first adhesive is W. 21 The negative electrode plate satisfies: (1) 1.0 ≤ W 21 / W 11 ≤2.0; (2) 1%≤W 11 ≤4%; (3) 4%≤W 21 ≤7%.

[0015] In some embodiments, the width of the first coating is W t mm, the negative electrode plate satisfies one of the following: (1) 1≤W t <3, 1.6≤W 21 / W 11 ≤2.0; (2) 3≤W t <6, 1.3≤W 21 / W 11 ≤1.6; (3) 6≤W t ≤9, 1.0≤W 21 / W 11 ≤1.3. The width of the first coating is small, and by further increasing the mass ratio of the first binder in the first coating, the volume expansion of the first coating can be better reduced.

[0016] In some embodiments, the negative electrode film layer includes a negative electrode conductive agent, and the mass percentage of the negative electrode conductive agent based on the total mass of the negative electrode film layer is W. 12 The first coating includes a first conductive agent, and based on the total mass of the first coating, the mass percentage of the first conductive agent is W. 22 The negative electrode plate satisfies: (1) 1.0 ≤ W 22 / W 12 ≤4.0; (2) 1%≤W 12 ≤5%; (3) 1%≤W 22 ≤5%.

[0017] In some embodiments, the relative friction coefficient between the negative electrode film layer and the negative electrode current collector is μ1, and the relative friction coefficient between the first coating layer and the negative electrode current collector is μ2. The negative electrode sheet satisfies: 0.75≤μ2 / μ1≤5, 0.05≤μ1≤0.20, 0.15≤μ2≤0.25. This reduces problems such as warping and powder shedding during rolling and cyclic charging and discharging, and prevents problems such as puncture of the negative electrode current collector or cracking during rolling.

[0018] In some embodiments, the porosity of the negative electrode film is P1, the porosity of the first coating is P2, and the negative electrode sheet satisfies: 1≤P2 / P1≤2, 20%≤P1≤38%, and 32%≤P2≤50%.

[0019] In some embodiments, the thickness of the negative electrode film is H1 μm, the thickness of the first coating is H2 μm, and the negative electrode sheet satisfies: 0.9 ≤ H1 / H2 ≤ 1.2. This reduces stress concentration at the boundary between the negative electrode film and the first coating.

[0020] In some embodiments, the specific surface area of ​​the negative electrode active material is 0.8 m². 2 / g to 2m 2 / g.

[0021] In some embodiments, the specific surface area of ​​the first material is 2m². 2 / g to 8m 2 / g. This can prevent the negative electrode slurry from migrating to the edge, reducing or even eliminating the thinning zone.

[0022] In some embodiments, the particle size Dn50 of the negative electrode active material is denoted as D1 μm, and the particle size Dn50 of the first material is denoted as D2 μm, where 0.25 ≤ D2 / D1 ≤ 1.5. This can improve the compaction density matching between the negative electrode film and the first coating layer, reducing stress concentration problems at the boundary between the negative electrode film and the first coating layer.

[0023] In some embodiments, the particle size Dn50 of the negative electrode active material is denoted as D1μm, and 10≤D1≤20.

[0024] In some embodiments, the particle size Dn50 of the first material is denoted as D2μm, where 5≤D2≤15. This allows for a combination of high capacity, good kinetic properties, and good slurry coating performance.

[0025] In some embodiments, the porosity of the first material is 38% to 50%. This can prevent the negative electrode slurry from migrating to the edges, reducing or even eliminating the thinning zone.

[0026] In some embodiments, the first material I D / I G It ranges from 0.8 to 1.4, I D The Raman shift in the Raman spectrum of the first material is 1350 ± 10 cm⁻¹ -1 The intensity of peak D at location, I G The Raman shift in the Raman spectrum of the first material is 1580 ± 10 cm⁻¹ -1 The intensity of the G peak at the specified location. This allows for a balance between the specific capacity and kinetic properties of the first material.

[0027] In some embodiments, the negative electrode active material I D / I G The value ranges from 0.08 to 0.30, I D The Raman shift in the Raman spectrum of the negative electrode active material is 1350±10 cm⁻¹ -1 The intensity of peak D at location, I G The Raman shift in the Raman spectrum of the negative electrode active material is 1580±10 cm⁻¹ -1 The intensity of the G peak at the specified location. This can improve the energy density of the secondary battery.

[0028] Secondly, this disclosure provides an electrical device that includes the secondary battery of the first aspect.

[0029] This disclosure has at least the following beneficial effects.

[0030] This disclosure provides a secondary battery and an electrical device. The negative electrode of the secondary battery includes a negative current collector, a negative electrode film, and a first coating. The first coating includes a first material and a first binder. The first material includes hard carbon. The electronic conductivity of the negative electrode film at 25°C is σ. e1 S / cm, the electronic conductivity of the first coating at 25°C is σ e2 S / cm, the negative electrode plate satisfies: 12.5≤σ e1 / σ e2 ≤250, where 10≤σ e1 With a value of ≤50, the negative electrode film has good electronic conductivity, which can reduce polarization. At the same time, the first coating has moderate electronic conductivity, which can not only compensate for the capacity at the edge of the negative electrode film, but also improve the local capacity mismatch caused by edge thinning, uneven coating, and positive electrode edge effect, and improve the metal deposition problem at the edge of the negative electrode film, but also improve the cycle performance, kinetic performance and reliability of the secondary battery.

[0031] The electrical equipment disclosed herein includes the secondary battery provided herein, and therefore has at least the same beneficial effects as a secondary battery. Attached Figure Description

[0032] To more clearly illustrate the technical solutions of the embodiments of this disclosure, the accompanying drawings used in the embodiments of this disclosure will be briefly described below. Obviously, the drawings described below are merely some embodiments of this disclosure. For those skilled in the art, other drawings can be obtained based on the drawings without any creative effort.

[0033] Figure 1 A schematic diagram of the structure of a negative electrode sheet provided in an embodiment of this disclosure is shown.

[0034] Figure 2A schematic diagram of the structure of a negative electrode sheet provided in an embodiment of this disclosure is shown.

[0035] The accompanying drawings are not necessarily drawn to scale.

[0036] The reference numerals in the attached figures are explained as follows: 111, negative electrode film layer; 112, first coating layer; 121, negative electrode body; 122, negative electrode tab; L, length direction; W, width direction; H, thickness direction. Detailed Implementation

[0037] To make the objectives, technical solutions, and advantages of this disclosure clearer, the technical solutions of this disclosure will be clearly and completely described below in conjunction with embodiments. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure. The embodiments described herein are illustrative in nature and are intended to provide a basic understanding of this disclosure. The embodiments of this disclosure should not be construed as limiting this disclosure. All other embodiments obtained by those skilled in the art based on the technical solutions and embodiments provided in this disclosure without inventive effort are within the scope of protection of this disclosure.

[0038] For the sake of brevity, this article only discloses a few specific numerical ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range, just as any upper limit can be combined with any other upper limit to form an unspecified range. Furthermore, each individually disclosed point or single value can itself serve as a lower or upper limit and be combined with any other point or single value or with other lower or upper limits to form an unspecified range.

[0039] Unless otherwise specified, all embodiments and optional embodiments of this disclosure may be combined with each other to form new technical solutions, and such technical solutions should be considered as included in the disclosure of this disclosure.

[0040] Unless otherwise specified, all technical features and optional technical features of this disclosure can be combined to form new technical solutions, and such technical solutions should be considered as included in the disclosure of this disclosure.

[0041] In this description, unless otherwise stated, "above" and "below" include the stated number.

[0042] In this description, unless otherwise stated, the terms “first,” “second,” etc., are used to distinguish different objects, rather than to describe a specific order or hierarchy.

[0043] Unless otherwise stated, the terminology used in this disclosure has its common meaning as understood by those skilled in the art. Unless otherwise stated, the values ​​of the parameters mentioned in this disclosure can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this disclosure). Unless otherwise stated, the test temperature for all parameters mentioned in this disclosure is 25°C and the test pressure is standard atmospheric pressure.

[0044] The list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms can mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another instance, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.

[0045] The term "multiple" refers to two or more.

[0046] The secondary battery disclosed herein is capable of charging and discharging independently.

[0047] A secondary battery includes a casing and electrode assemblies, with the electrode assemblies housed within the casing. The casing forms a receiving space. This receiving space can be used to house the electrode assemblies.

[0048] The outer casing can be a soft-pack material or a hard-pack material, and this disclosure does not limit the embodiments. For example, the outer casing is an aluminum-plastic film or a steel-plastic film to form a soft-pack secondary battery, or the outer casing is a steel shell or an aluminum shell to form a hard-pack secondary battery.

[0049] The electrode assembly includes a negative electrode, a positive electrode, and a separator. The separator is located between the negative and positive electrodes and mainly serves to prevent short circuits between the positive and negative electrodes, while allowing active ions to pass through.

[0050] The secondary battery disclosed herein can be a lithium-ion secondary battery.

[0051] Currently, during the negative electrode slurry coating process, there is a problem where the negative electrode slurry near the edge in the width direction flows outward into the uncoated area. This results in a reduction in the mass and thickness of the negative electrode slurry at the edge, forming a thinned region after drying. The thinned region has low capacity and is prone to metal precipitation, affecting the cycle performance and kinetic performance of the secondary battery. Furthermore, the wider the thinned region, the more significant the impact on the cycle performance and kinetic performance of the secondary battery.

[0052] In view of this, the present disclosure provides a secondary battery that improves the cycle performance and kinetic performance of the secondary battery by adjusting the parameters of the negative electrode.

[0053] The secondary battery provided in this embodiment includes an electrode assembly, which includes a negative electrode, a positive electrode, and a separator, with the separator located between the negative electrode and the positive electrode.

[0054] The negative electrode includes a negative current collector, a negative electrode film, and a first coating. The negative current collector includes a negative electrode body and a negative electrode tab extending from one end of the negative electrode body. The negative electrode body includes a coating region and a transition region, with the transition region disposed between the negative electrode tab and the coating region. The negative electrode film is disposed in the coating region, and the first coating is at least partially disposed in the transition region. The negative electrode film includes a negative electrode active material and a negative electrode binder, with the negative electrode active material including graphite. The positive electrode includes a positive current collector and a positive electrode film disposed on at least one side of the positive current collector. Along the thickness direction of the positive electrode, the orthographic projection of the first coating does not overlap with the orthographic projection of the positive electrode film.

[0055] The first coating comprises a first material and a first binder, wherein the first material comprises hard carbon.

[0056] The electronic conductivity of the negative electrode film at 25℃ is σ. e1 S / cm, the electronic conductivity of the first coating at 25°C is σ e2 S / cm, the negative electrode plate satisfies: 12.5≤σ e1 / σ e2 ≤250, where 10≤σ e1 ≤50.

[0057] To address the issue of thinning at the edge of the negative electrode film, existing technologies involve coating the edge of the negative electrode paste with an insulating ceramic paste. This can reduce the width of the thinned area and improve metal deposition to some extent, but the improvement effect is not significant and needs further improvement.

[0058] This disclosure discloses a first coating layer between the negative electrode tab and the negative electrode film layer. The first coating layer includes hard carbon, which can extract and insert active ions, giving the first coating layer a certain capacity. This can fundamentally improve the problem of low capacity at the edge of the negative electrode film layer, thereby better improving the metal deposition problem. Hard carbon has good kinetic performance and can also improve the kinetic performance of the secondary battery. In addition, the first coating slurry containing hard carbon dries quickly and can form a baffle to restrict the flow of the negative electrode slurry, thereby reducing the width of the thinning zone or even preventing the formation of the thinning zone.

[0059] The negative electrode film layer satisfies 10 ≤ σ e1 ≤50, which gives the negative electrode film good electronic conductivity and can reduce polarization.

[0060] σ e1 / σ e2 It is the ratio of the electronic conductivity of the negative electrode film to the electronic conductivity of the first coating, which reflects the electronic conduction performance of the first coating.

[0061] σ e1 / σ e2 An excessively high electronic conductivity (σ) indicates that the first coating has weak electronic conductivity and strong electronic blocking properties. Although hard carbon particles themselves have the ability to extract and insert active ions, the weak electronic conductivity of the first coating results in high electronic conduction resistance within the coating. Since electronic conduction is a prerequisite for the insertion and extraction of active ions, the electronic conductivity σ of the first coating... e2 Small size and weak electronic conductivity lead to insufficient electron supply at local sites, resulting in increased local ohmic polarization, increased DC internal resistance, deteriorated dynamics under high current, and easy local metal deposition during charging. At the same time, the lack of electrons for hard carbon particles at local sites also reduces the capacity utilization of the first coating.

[0062] σ e1 / σ e2 If the width is too small, it indicates that the first coating has good electronic conductivity and weak electronic blocking effect. Usually, the width of the negative electrode film is larger than that of the positive electrode film. The good electronic conductivity of the first coating may lead to the concentration of edge current, which may increase the risk of short circuit between the positive and negative electrodes and affect the reliability of the secondary battery. In addition, it will also lead to an imbalance between electronic and ion conduction in the first coating, increase concentration polarization, and deteriorate cycle performance and kinetic performance.

[0063] This disclosure makes the first material include hard carbon, 12.5≤σ e1 / σ e2 ≤250, 10≤σ e1 With a value of ≤50, the negative electrode film has good electronic conductivity, which can reduce polarization. At the same time, the first coating has moderate electronic conductivity, which can not only compensate for the capacity at the edge of the negative electrode film, but also improve the local capacity mismatch caused by edge thinning, uneven coating, and positive electrode edge effect, and improve the metal deposition problem at the edge of the negative electrode film, but also improve the cycle performance, kinetic performance and reliability of the secondary battery.

[0064] As an example, σ e1 / σ e2 It can be a range of 12.5, 15, 20, 25, 30, 40, 50, 60, 70, 80, 90, 100, 125, 150, 200, 250, or any of the above values.

[0065] Alternatively, in some embodiments, 15 ≤ σ e1 / σ e2≤250, 15≤σ e1 / σ e2 ≤200, 25≤σ e1 / σ e2 ≤200, 25≤σ e1 / σ e2 ≤150, 50≤σ e1 / σ e2 ≤150.

[0066] As an example, σ e1 It can be a range of 10, 15, 20, 25, 30, 35, 40, 45, 50, or any of the above values.

[0067] Alternatively, in some embodiments, 15 ≤ σ e1 ≤30.

[0068] In some embodiments, 0.1 ≤ σ e2 ≤1.6, for example, can be 0.1, 0.2, 0.4, 0.6, 0.8, 1, 1.2, 1.4, 1.6, or any of the above values.

[0069] σ e2 The first coating has weak electronic conductivity and strong electronic blocking effect. Local sites are prone to insufficient electron supply, which can lead to increased local ohmic polarization, increased DC internal resistance, deterioration of kinetics under high current, and local metal deposition during charging. At the same time, the hard carbon particles at local sites cannot obtain electrons, which will also reduce the capacity utilization of the first coating.

[0070] σ e2 The large size of the first coating, with its good electronic conductivity and weak electronic barrier effect, may lead to concentrated edge current, increasing the risk of short circuits between the positive and negative electrodes and affecting the reliability of the secondary battery. It may also increase concentration polarization, affecting the cycle performance and kinetic performance of the secondary battery.

[0071] σ e2 Within the aforementioned range, the first coating has a moderate electronic conductivity, which can not only compensate for the capacity at the edge of the negative electrode film, improve the local capacity mismatch of the negative electrode film, and improve the metal deposition problem at the edge of the negative electrode film, but also improve the cycle performance, kinetic performance and reliability of the secondary battery.

[0072] The capacity per unit area of ​​the first coating is Q2 mAh / cm². 2 The capacity per unit area of ​​the positive electrode film is Q. p mAh / cm 2 .

[0073] In some embodiments, 1.05 ≤ Q2 / Q p≤1.30, for example, can be 1.05, 1.10, 1.15, 1.20, 1.25, 1.30, or any range of the above values.

[0074] Q2 / Q p The first coating has a small capacity per unit area, resulting in a weak compensation effect on the capacity at the edge of the negative electrode film and a weak improvement effect on metal deposition at the edge.

[0075] Q2 / Q p Large, excessive capacity per unit area in the first coating will reduce energy density and may also increase the first irreversible capacity loss of hard carbon.

[0076] Q2 / Q p Within the aforementioned range, it can better improve the local capacity mismatch of the negative electrode film, improve the metal deposition problem at the edge of the negative electrode film, and improve cycle performance and kinetic performance, while not affecting the energy density and initial coulombic efficiency of the secondary battery.

[0077] Alternatively, 1.10 ≤ Q2 / Q p ≤1.20.

[0078] In some embodiments, 10.4 ≤ (σ e1 / σ e2 ) / (Q2 / Q p )≤227.3, for example, it can be 10.4, 12, 16, 20, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 175, 200, 227.3, or any range of the above values.

[0079] (σ) e1 / σ e2 ) / (Q2 / Q p This reflects the degree of matching between the electronic blocking effect and the capacity compensation effect of the first coating.

[0080] (σ) e1 / σ e2 ) / (Q2 / Q p The small size of the hard carbon leads to weak electron blocking and strong capacity compensation, which may cause edge current concentration, increasing the risk of short circuits between the positive and negative electrodes and affecting the reliability of the secondary battery. It will also increase concentration polarization, affecting the cycle performance and kinetic performance of the secondary battery. Furthermore, it will reduce energy density and increase the first irreversible capacity loss of hard carbon.

[0081] (σ) e1 / σ e2 ) / (Q2 / Q pThe large size of the coating results in strong electron blocking and weak capacity compensation. This leads to insufficient electron supply at local sites, which can cause increased local polarization, increased DC internal resistance, deterioration of kinetics under high current, and easy local metal deposition during charging. At the same time, the lack of electrons for hard carbon particles at local sites can also reduce the capacity utilization of the first coating.

[0082] (σ) e1 / σ e2 ) / (Q2 / Q p Within the aforementioned range, the electron blocking effect and capacity compensation effect of the first coating can be balanced, the metal precipitation problem at the edge position can be improved, and the cycle performance and kinetic performance of the secondary battery can be improved, while not affecting the energy density and initial coulombic efficiency of the secondary battery.

[0083] Alternatively, 20 ≤ (σ e1 / σ e2 ) / (Q2 / Q p )≤175, 20≤(σ e1 / σ e2 ) / (Q2 / Q p ≤150.

[0084] In some embodiments, a fusion region is formed between the negative electrode film layer and the first coating layer, and the width of the fusion region is 1 mm to 3 mm.

[0085] The fusion zone is generated when the negative electrode slurry and the first coating slurry flow together during coating.

[0086] In some embodiments, both surfaces of the negative electrode current collector in the thickness direction are provided with a negative electrode film layer and a first coating layer.

[0087] In some embodiments, the two first coatings form fusion regions of different widths with the negative electrode film layer.

[0088] In some embodiments, the boundaries of the two first coatings away from the negative electrode film are offset from each other along the width direction of the negative electrode current collector.

[0089] In some embodiments, a first coating is provided on both surfaces of the negative electrode current collector in the thickness direction. Along the thickness direction of the negative electrode current collector, the orthographic projections of the two first coatings parallel to the length direction of the negative electrode current collector and away from the boundary of the negative electrode film layer do not coincide.

[0090] This reduces stress concentration in the thickness direction of the negative electrode sheet, and lowers the risk of cracks, powdering, and peeling during rolling and / or winding.

[0091] like Figure 1 and Figure 2As shown, the negative electrode sheet includes a negative current collector, a negative electrode film layer 111, and a first coating layer 112. The negative current collector includes a negative electrode body portion 121 and a negative electrode tab 122 extending from one end of the negative electrode body portion 121. The negative electrode body portion 121 includes a coating area and a transition area. The transition area is disposed between the negative electrode tab and the coating area. The negative electrode film layer 111 is disposed in the coating area. The first coating layer 112 is at least partially disposed in the transition area. The negative electrode film layer 111 and the first coating layer 112 are disposed on both surfaces in the thickness direction H of the negative current collector. The boundaries of the two first coating layers 112 away from the negative electrode film layer 111 are staggered from each other along the width direction W of the negative current collector. Along the thickness direction H of the negative current collector, the orthographic projections of the two first coating layers 112 parallel to the length direction L of the negative current collector and away from the boundary of the negative electrode film layer do not coincide.

[0092] The electronic conductivity and ionic conductivity of the negative electrode film and the first coating can be adjusted by regulating the types and / or contents of each component in the negative electrode film and the first coating.

[0093] In some embodiments, the specific surface area of ​​the negative electrode active material is 0.8 m². 2 / g to 2m 2 / g, for example, can be 0.8m 2 / g, 0.9m 2 / g, 1m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g, 1.6m 2 / g, 1.7m 2 / g, 1.8m 2 / g, 1.9m 2 / g, 2.0m 2 / g, or any range of the above values.

[0094] In some embodiments, the specific surface area of ​​the first material is 2m². 2 / g to 8m 2 / g, for example, can be 2m 2 / g, 2.5m 2 / g、3m 2 / g, 3.5m 2 / g、4m 2 / g, 4.5m 2 / g、5m 2 / g, 5.5m 2 / g、6m 2 / g, 6.5m 2 / g、7m 2 / g, 7.5m2 / g、8m 2 / g, or any range of the above values.

[0095] When the specific surface area of ​​the first material is within the above range, the particle surface can adsorb more first binder, and the flow resistance of the first coating slurry is improved after wet film formation. This can prevent the negative electrode slurry from migrating to the edge and reduce or even eliminate the thinning zone.

[0096] In some embodiments, the particle size Dn50 of the negative electrode active material is denoted as D1μm, the particle size Dn50 of the first material is denoted as D2μm, and 0.25≤D2 / D1≤1.5. For example, D2 / D1 can be 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, or any range of the above values.

[0097] Within the above range, D2 / D1 can improve the compaction density matching between the negative electrode film and the first coating, reducing stress concentration problems at the boundary between the negative electrode film and the first coating.

[0098] In some embodiments, the particle size Dn50 of the negative electrode active material is denoted as D1μm, 10≤D1≤20, for example, D1 can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, or any range of the above values.

[0099] In some embodiments, the particle size Dn50 of the first material is denoted as D2μm, where 5≤D2≤15. For example, D2 can be 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, or any range of the above values.

[0100] The particle size Dn50 of the first material is within the above range, which can combine high capacity, good kinetic properties and good slurry coating properties.

[0101] In some embodiments, the porosity of the first material is 38% to 50%, for example, it can be 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, or any range of the above values.

[0102] The porosity of the first material is within the above range, the specific surface area of ​​the particles is high, and the particle surface can adsorb more first binder. After the first coating slurry wet film is formed, the anti-flow ability is improved, thereby preventing the negative electrode slurry from migrating to the edge and reducing or even eliminating the thinning zone.

[0103] In some embodiments, the first material I D / I GIt ranges from 0.8 to 1.4, I D The Raman shift in the Raman spectrum of the first material is 1350 ± 10 cm⁻¹ -1 The intensity of peak D at location, I G The Raman shift in the Raman spectrum of the first material is 1580 ± 10 cm⁻¹ -1 The intensity of the G peak at the location, for example, I D / I G It can be a range of 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, or any of the above values.

[0104] First Material I D / I G Within the aforementioned range, it is possible to balance the specific capacity and kinetic properties of the first material.

[0105] In some embodiments, the negative electrode active material I D / I G The value ranges from 0.08 to 0.30, I D The Raman shift in the Raman spectrum of the negative electrode active material is 1350±10 cm⁻¹ -1 The intensity of peak D at location, I G The Raman shift in the Raman spectrum of the negative electrode active material is 1580±10 cm⁻¹ -1 The intensity of the G peak at the location, for example, I D / I G It can be 0.08, 0.10, 0.12, 0.14, 0.16, 0.18, 0.20, 0.22, 0.24, 0.26, 0.28, 0.30, or any range of the above values.

[0106] I of negative electrode active material D / I G Within the aforementioned range, high specific capacity can improve the energy density of secondary batteries.

[0107] Based on the total mass of the negative electrode film, the mass percentage of the negative electrode binder is W. 11 .

[0108] Based on the total mass of the first coating, the mass percentage of the first adhesive is W. 21 .

[0109] In some embodiments, 1.0 ≤ W 21 / W 11 ≤2.0, for example, can be 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, or any range of the above values.

[0110] Alternatively, 1.0 < W21 / W 11 ≤2.0.

[0111] The first binder accounts for a higher percentage of the mass in the first coating, which reduces the volume expansion of the first coating.

[0112] In some embodiments, 1%≤W 11 ≤4%, for example, can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, or any range of the above values.

[0113] In some embodiments, 4%≤W 21 ≤7%, for example, can be 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, 5.2%, 5.4%, 5.6%, 5.8%, 6%, 6.2%, 6.4%, 6.6%, 6.8%, 7%, or any range of the above values.

[0114] The width of the first coating is W t mm.

[0115] In some embodiments, 1≤W t ≤9.

[0116] In some embodiments, the negative electrode plate satisfies: 1 ≤ W t <3, 1.6≤W 21 / W 11 ≤2.0.

[0117] In some embodiments, the negative electrode plate satisfies: 3≤W t <6, 1.3≤W 21 / W 11 ≤1.6.

[0118] In some embodiments, the negative electrode plate satisfies: 6 ≤ W t ≤9, 1.0≤W 21 / W 11 ≤1.3.

[0119] The first coating has a small width, and by further increasing the mass ratio of the first binder in the first coating, the volume expansion of the first coating can be better reduced.

[0120] In some embodiments, the negative electrode binder includes at least one selected from styrene-butadiene rubber (SBR), polyacrylic acid and its salts, polymethacrylic acid and its salts, polyacrylamide, polyvinyl alcohol, sodium alginate, carboxymethyl chitosan, styrene-acrylic resin, and derivatives thereof. Derivatives generally refer to products derived from polymers in which hydrogen atoms or groups of atoms are replaced by other atoms or groups of atoms.

[0121] In some embodiments, the first binder includes at least one selected from styrene-butadiene rubber (SBR), polyacrylic acid and its salts, polymethacrylic acid and its salts, polyacrylamide, polyvinyl alcohol, sodium alginate, carboxymethyl chitosan, styrene-acrylic resin, and derivatives thereof. Derivatives generally refer to products derived from polymers in which hydrogen atoms or groups of atoms are replaced by other atoms or groups of atoms.

[0122] In some embodiments, the negative electrode film layer includes a negative electrode conductive agent, and the mass percentage of the negative electrode conductive agent based on the total mass of the negative electrode film layer is W. 12 .

[0123] In some embodiments, the first coating includes a first conductive agent, and the mass percentage of the first conductive agent based on the total mass of the first coating is W. 22 .

[0124] In some embodiments, 1.0 ≤ W 22 / W 12 ≤4.0, for example, can be 1.0, 1.2, 1.4, 1.6, 1.8, 2.0, 2.2, 2.4, 2.6, 2.8, 3.0, 3.2, 3.4, 3.6, 3.8, 4.0, or any range of the above values.

[0125] Alternatively, 1.0 < W 22 / W 12 ≤4.0.

[0126] In some embodiments, 1%≤W 12 ≤5%, for example, can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, or any range of the above values.

[0127] In some embodiments, 1%≤W 22 ≤5%, for example, can be 1%, 1.2%, 1.4%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.6%, 2.8%, 3%, 3.2%, 3.4%, 3.6%, 3.8%, 4%, 4.2%, 4.4%, 4.6%, 4.8%, 5%, or any range of the above values.

[0128] In some embodiments, the negative electrode conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon fiber, graphene, and carbon nanotubes.

[0129] In some embodiments, the first conductive agent includes at least one of conductive carbon black, acetylene black, Ketjen black, carbon fiber, graphene, and carbon nanotubes.

[0130] In some embodiments, the negative electrode film layer may further include a negative electrode dispersant, thereby improving the film-forming quality of the negative electrode film layer. As an example, the negative electrode dispersant may include, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC-Na) and its derivatives. Derivatives generally refer to products derived from polymers in which hydrogen atoms or groups of atoms are replaced by other atoms or groups of atoms (e.g., amino groups).

[0131] In some embodiments, the first coating may further include a first dispersant, thereby improving the film-forming quality of the first coating. As an example, the first dispersant may include, but is not limited to, at least one of sodium carboxymethyl cellulose (CMC-Na) and its derivatives. Derivatives generally refer to products derived from polymers in which hydrogen atoms or groups of atoms are replaced by other atoms or groups of atoms (e.g., amino groups).

[0132] The relative friction coefficient between the negative electrode film and the negative electrode current collector is μ1, and the relative friction coefficient between the first coating and the negative electrode current collector is μ2.

[0133] By adjusting the surface roughness and surface energy of the negative electrode current collector, the relative friction coefficient between the negative electrode film and the negative electrode current collector, as well as the relative friction coefficient between the first coating and the negative electrode current collector, can be adjusted.

[0134] The relative coefficient of friction between the negative electrode film and the negative electrode current collector can be adjusted by regulating the composition and / or surface roughness of the negative electrode film.

[0135] The relative coefficient of friction between the first coating and the negative electrode current collector can be adjusted by adjusting the composition and / or surface roughness of the first coating.

[0136] In some embodiments, 0.75 ≤ μ2 / μ1 ≤ 5.

[0137] As an example, μ2 / μ1 can be 0.75, 1, 1.25, 1.5, 1.75, 2, 2.25, 2.5, 2.75, 3, 3.25, 3.5, 3.75, 4, 4.25, 4.5, 4.75, 5, or any of the above values.

[0138] Within the above range, μ2 / μ1 can reduce stress concentration at the boundary between the negative electrode film and the first coating layer.

[0139] In some embodiments, 0.05 ≤ μ1 ≤ 0.20.

[0140] As an example, μ1 can be 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, or any range of the above values.

[0141] In some embodiments, 0.15 ≤ μ2 ≤ 0.25.

[0142] As an example, μ2 can be 0.15, 0.16, 0.17, 0.18, 0.19, 0.20, 0.21, 0.22, 0.23, 0.24, 0.25, or any range of the above values.

[0143] Within the above range, μ2, the adhesion between the first coating and the negative electrode current collector is good, which can reduce problems such as lifting and powder falling off during rolling and cyclic charging and discharging; at the same time, the surface roughness of the first coating is moderate, and there will be no problems such as the negative electrode current collector being punctured or cracked during rolling.

[0144] In some embodiments, 0.75≤μ2 / μ1≤5, 0.05≤μ1≤0.20, and 0.15≤μ2≤0.25.

[0145] The porosity of the negative electrode film is P1, and the porosity of the first coating is P2.

[0146] In some embodiments, 1≤P2 / P1≤2.

[0147] As an example, P2 / P1 can be 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, or any range of the above values.

[0148] Alternatively, 1 < P2 / P1 ≤ 2.

[0149] The first coating has high porosity, good dynamic performance, and can also reduce the volume expansion of the first coating.

[0150] In some embodiments, 20% ≤ P1 ≤ 38%.

[0151] As an example, P1 can be 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, or any of the above values.

[0152] In some embodiments, 32% ≤ P2 ≤ 50%.

[0153] As an example, P2 can be 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, or any of the above values.

[0154] In some embodiments, the negative electrode sheet satisfies: 1≤P2 / P1≤2, 25%≤P1≤38%, and 38%≤P2≤50%.

[0155] Optionally, the negative electrode sheet satisfies: 1 < P2 / P1 ≤ 2, 25% ≤ P1 ≤ 38%, and 38% ≤ P2 ≤ 50%.

[0156] The thickness of the negative electrode film is H1μm, and the thickness of the first coating is H2μm.

[0157] In some embodiments, 0.9 ≤ H1 / H2 ≤ 1.2, for example, can be 0.9, 0.95, 1, 1.05, 1.1, 1.15, 1.2, or any range of the above values.

[0158] Within the above range, H1 / H2 can reduce stress concentration at the boundary between the negative electrode film and the first coating layer.

[0159] The negative electrode current collector includes a negative electrode body and a negative electrode tab extending from one end of the negative electrode body.

[0160] In some embodiments, the negative electrode body of the negative electrode current collector may be plate-shaped or foil-shaped, and the present disclosure does not limit this.

[0161] In some embodiments, the negative electrode tab can be rectangular or trapezoidal in shape.

[0162] In some embodiments, the number of negative electrode tabs is one or more.

[0163] In some embodiments, the materials of the negative electrode body and the negative electrode tab of the negative electrode current collector are not particularly limited, and materials with good electronic conductivity can be selected. For example, elements or alloys containing at least one element selected from C, Cu, Ni, Fe, V, Nb, Ti, Cr, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, and Ag (such as stainless steel) can be used. Composite materials formed by plating different conductive materials on a conductive material can also be used, for example, Cu can be plated on Fe, and Ni can be plated on Cu.

[0164] Optionally, the negative electrode body is made of Cu or Ni.

[0165] Optionally, the negative electrode tab is made of Cu or Ni.

[0166] In some embodiments, the negative electrode tab can be formed by welding or die cutting.

[0167] In some embodiments, the method for preparing the negative electrode sheet includes the following steps: coating the negative electrode slurry and the first coating slurry on at least one side of the negative electrode current collector, and obtaining the negative electrode sheet through processes such as drying and compaction.

[0168] Optionally, the negative electrode slurry and the first coating slurry are applied simultaneously in one process.

[0169] The preparation method of negative electrode slurry includes the following steps: dispersing negative electrode active material, negative electrode conductive agent, negative electrode binder, negative electrode dispersant, etc. in a solvent to form negative electrode slurry.

[0170] The preparation method of the first coating slurry includes the following steps: dispersing the first material, the first conductive agent, the first binder, the first dispersant, etc. in a solvent to form the first coating slurry.

[0171] The solvent in the above slurry may include, but is not limited to, at least one of water, ethanol, acetone, butanone, dimethylformamide, N-methylpyrrolidone, diethylformamide, dimethyl sulfoxide, and tetrahydrofuran.

[0172] The coating method can be any coating method known in the art, such as extrusion coating, gravure coating, microgravure coating, spraying, transfer coating, etc. The embodiments disclosed herein are not limited in this respect.

[0173] [Positive electrode plate] The materials, composition, and manufacturing methods of the positive electrode may include any techniques known in the prior art.

[0174] In some embodiments, the positive electrode includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector, the positive electrode film layer including a positive active material.

[0175] In some embodiments, the positive current collector may be plate-shaped or foil-shaped, and the present disclosure does not limit this.

[0176] In some embodiments, the material of the positive current collector is not particularly limited, and a material with electronic conductivity can be selected. For example, an element or alloy containing at least one element selected from C, Ti, Cr, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, and Al (e.g., stainless steel) can be used.

[0177] In some embodiments, the positive electrode active material is capable of de-intercalating and intercalating lithium ions, and the positive electrode active material includes at least one of lithium phosphate and lithium transition metal oxide.

[0178] By way of example, the positive electrode active material may include, but is not limited to, at least one of lithium iron phosphate, lithium manganese phosphate, lithium cobalt phosphate, iron pyrophosphate, lithium cobalt oxide, spinel-type lithium manganate, spinel-type lithium nickel manganate, layered lithium manganate, lithium nickelate, lithium niobate, lithium ferrate, lithium magnesate, lithium calciate, lithium cuprate, lithium zincate, lithium molybdate, lithium tantalate, lithium tungstate, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, lithium-rich materials (e.g., lithium-rich nickel cobalt manganese oxide), manganese oxide, vanadium oxide, sulfur oxide, silicate oxide, and respective modified compounds thereof.

[0179] Optionally, the positive electrode active material may include at least one of lithium iron phosphate, lithium cobalt oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese oxide, spinel-type lithium nickel manganate, and respective modified compounds thereof.

[0180] By way of example, the molecular formula of the lithium nickel cobalt aluminum oxide may be LiNi x Co y Al 1-x-y O2, 0<x<1, 0<y<1, 0<x+y<1, for example, may include but is not limited to LiNi 0.8 Co 0.15 Al 0.05 O2.

[0181] By way of example, the molecular formula of the lithium nickel cobalt manganese oxide may be LiNi x Co y Mn 1-x-y O2, 0<x<1, 0<y<1, 0<x+y<1, for example, may include but is not limited to at least one of LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2.

[0182] By way of example, the spinel-type lithium nickel manganate may include but is not limited to LiNi 0.5 Mn 1.5 O4.

[0183] The modified compound of each of the above positive electrode active materials may be a positive electrode active material modified by doping modification, surface coating modification, or simultaneous doping and coating modification.

[0184] In some embodiments, the positive electrode film layer further includes a positive electrode conductive agent. The positive electrode conductive agent may include conductive carbon powder. As an example, the positive electrode conductive agent may include, but is not limited to, at least one of conductive carbon black, acetylene black, Ketjen black, carbon fiber, graphene, carbon nanotubes, graphite, hard carbon, soft carbon, and glassy carbon.

[0185] In some embodiments, the positive electrode film layer further includes a positive electrode binder. The positive electrode binder may include, but is not limited to, at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene-propylene terpolymer, ethylene-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and polyvinyl alcohol (PVA).

[0186] The positive electrode sheet can be prepared according to conventional methods in the art. Typically, a positive electrode active material, a positive electrode conductive agent, a positive electrode binder, etc., are dispersed in a solvent to form a positive electrode slurry. The positive electrode slurry is then coated onto at least one side of a positive electrode current collector, and the positive electrode sheet is obtained through processes such as drying and compaction. The solvent can be N-methylpyrrolidone (NMP), but this disclosure is not limited thereto.

[0187] The coating method can be any coating method known in the art, such as extrusion coating, gravure coating, microgravure coating, spraying, transfer coating, etc. The embodiments disclosed herein are not limited in this respect.

[0188] [Isolation Component] The separator is located between the positive and negative electrodes, and its main function is to prevent short circuits between the positive and negative electrodes, while allowing active ions to pass through.

[0189] In some embodiments, the separator is a separator membrane.

[0190] In some embodiments, the separating membrane includes a base membrane. This disclosure does not impose any particular limitation on the type of base membrane; any known porous membrane with good chemical and mechanical stability can be selected.

[0191] In some embodiments, the base film may be made of one or more of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The base film may be a single-layer film or a multi-layer composite film. When the base film is a multi-layer composite film, the materials of each layer may be the same or different.

[0192] In some embodiments, the separator further includes a ceramic layer disposed on at least one side of the base membrane.

[0193] Electrolyte In some embodiments, the secondary battery further includes an electrolyte, which comprises an electrolyte salt and a solvent. The types of electrolyte salt and solvent are not specifically limited and can be selected according to requirements.

[0194] In some embodiments, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalate borate (LiDFOB), and lithium dioxalate borate (LiBOB). One of the above electrolyte salts may be used alone, or two or more may be used simultaneously.

[0195] In some embodiments, the solvent may include at least one of carbonate compounds, carboxylic acid ester compounds, ether compounds, and sulfone compounds. As examples, the solvent may include, but is not limited to, ethylene carbonate (EC), fluoroethylene carbonate (FEC), vinylene carbonate (VC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), and methyl propionate (...). At least one of the following solvents: MP, ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), γ-butyrolactone, sulfolane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), methyl sulfolane, dimethyl sulfoxide, 2-methyltetrahydrofuran, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxyethane, 1,2-diethoxyethane, dimethyl ether, diethyl ether, nitromethane, and N,N-dimethylformamide. One of the above solvents may be used alone, or two or more may be used simultaneously.

[0196] The electrolyte can be prepared according to conventional methods in the art. For example, the solvent, electrolyte salt, and other components can be mixed evenly to obtain the electrolyte. There are no particular restrictions on the order in which the materials are added; for example, the electrolyte salt and other components can be added to the solvent and mixed evenly to obtain the electrolyte.

[0197] [Testing Method] The electronic conductivity of the negative electrode film and the first coating layer is tested using the four-probe method. The test temperature is 25℃. During testing, the negative electrode current collector needs to be stripped. The testing equipment can be a four-probe tester. During testing, the four probes of the four-probe tester are pressed vertically and evenly onto the dry negative electrode film or the first coating layer. The current parameters are set, the instrument is started, and the obtained potential difference and current value are recorded. Then, the electronic conductivity of the negative electrode film and the electronic conductivity of the first coating layer are calculated. Multiple tests (e.g., more than 5 times) can be performed, and the average value is taken as the test result.

[0198] The capacity per unit area of ​​the first coating can be tested as follows: The negative electrode is removed from the secondary battery, a sample is taken from the first coating location, and assembled into a coin cell for testing. A lithium sheet is used as the counter electrode, separated by a separator. Both the separator and the electrolyte are obtained from the secondary battery. The battery is then discharged to 0.01V (vs. Li) at a current density of 0.1C. + / Li), and then charged to 2V at a current density of 0.1C (vs. Li). + The resulting charging capacity ( / Li) is the capacity of the first coating. The capacity per unit area of ​​the first coating = capacity of the first coating / sample area.

[0199] The capacity per unit area of ​​the positive electrode film can be tested as follows: The positive electrode sheet is disassembled from a secondary battery, sampled, and assembled into a coin cell for testing. A lithium sheet is used as the counter electrode, separated by a separator. Both the separator and the electrolyte are obtained from the secondary battery. The battery is then charged at a current density of 0.1C to the upper cutoff voltage, and then discharged at a current density of 0.1C to the lower cutoff voltage. The resulting discharge capacity is the positive electrode capacity. The capacity per unit area of ​​the positive electrode film = positive electrode capacity / sample area.

[0200] In the aforementioned capacity test, freshly prepared electrolyte can be used as a sample, or the electrolyte obtained from a disassembled secondary battery at 0% SOC can be used as a sample. An exemplary method for obtaining the electrolyte from a secondary battery includes the following steps: disassembling the secondary battery at 0% SOC, centrifuging the electrode assembly (including the positive electrode, negative electrode, and separator) at a speed of ≥5000 rpm, and repeatedly collecting the electrolyte until no obvious liquid remains after centrifugation.

[0201] In this disclosure, the relative friction coefficient between the negative electrode film layer and the negative electrode current collector, and the relative friction coefficient between the first coating layer and the negative electrode current collector are both interlayer relative friction coefficients, which are different from the planar sliding friction coefficient of the outer surface and can be tested according to the following method.

[0202] (1) Equipment The equipment employs a servo-controlled closed-loop high-precision electronic universal testing machine or a lithium battery-specific micro-friction reciprocating testing machine, and is equipped with a real-time displacement feedback system using an optical grating ruler. The main parameters of the equipment are as follows: 1. Displacement resolution: 0.1μm, repeatability ≤1μm, can accurately control millimeter-level and micrometer-level micro-slip strokes, with no overtravel or backtravel errors; 2. Speed ​​control range: 0.001 mm / min to 500 mm / min, with speed control accuracy better than ±0.5%; 3. Equipped with reciprocating sliding program, end-point buffer deceleration function, and backlash-free rigid clamping fixture; 4. Supporting equipment: constant temperature electrolyte immersion chamber, uniformly distributed planar pressure fixture, graphite copper-plated simulated electrode slider, and slider contact surface roughness Ra of 0.8μm.

[0203] (2) Prepare the sample 1. Disassemble the negative electrode sheet from the secondary battery, cut the sample, and prepare no less than 5 sets of parallel samples.

[0204] 2. Completely immerse the sample in the electrolyte of the secondary battery (the secondary battery can be disassembled and the electrolyte obtained by centrifugation), and seal and immerse at a constant temperature of 25°C for 2 hours to ensure that the internal pores and interlayer gaps of the sample are fully saturated.

[0205] 3. Remove the sample and gently absorb the free electrolyte from the outer surface of the sample using electrolyte-resistant dust-free filter paper, retaining the electrolyte film at the interlayer interface and eliminating dry areas at the interface.

[0206] 4. Along the bonding interface of the sample, gently pre-peel 5mm to 10mm at the end of the sample. This is only used as the upper clamping and fixing section. The operation should be gentle throughout. Do not stretch or tear the effective bonding area to ensure that the bonding interface of the sample is intact, undamaged, and without pre-detachment.

[0207] 5. Place the sample in a dust-free constant temperature environment at 25℃ and humidity of 40% to 60% for 30 minutes to eliminate cutting stress, curling deformation and electrostatic interference.

[0208] (3) Test parameters 1. Sliding mode: Horizontal reciprocating micro-shear sliding, without unidirectional continuous peeling load; 2. Effective sliding stroke: 0.5mm; 3. Slip rate: 1 mm / min; 4. Positive compressive force: 0.3MPa-0.8MPa uniformly distributed pressure; 5. Pre-compression settling time: 30 min; 6. Traction angle: Fixed 180° pure horizontal traction, only generating interfacial shear force, and cannot interfere with the component force; 7. Test temperature: 25℃; 8. Cyclic test procedure: Each test is repeated 100 times, discarding the first 10 data points and selecting steady-state data from the 11th to the 100th test for statistical analysis.

[0209] (4) Data Judgment 1. Acceptance criteria: The fluctuation range of shear friction force in steady-state cycles from the 11th to the 100th cycle is ≤ ±10%, with no cliff-like stress attenuation, intact bonding interface, and only interfacial elastic shear expansion and contraction of the adapted electrode sheet. 2. Failure criteria: A sustained and significant drop in friction force, such as a decrease of >20%, indicates micro-debonding at the bonding interface or structural failure.

[0210] The coefficient of friction μ is tested using the following formula: μ=F f / F N F f To collect the horizontal friction force, F N The normal pressure is precisely and constantly applied through a uniformly distributed planar pressure fixture.

[0211] The porosity of the negative electrode film and the first coating layer can be tested as follows: Disassemble the negative electrode sheet from a secondary battery at 0% SOC. Cut 30 small circular pieces of a certain diameter from the negative electrode film and the first coating layer. Based on the principle of gas adsorption, using helium as the medium, measure the true volume V2 of the 30 small circular pieces using a true density meter (such as the AccuPyc II 1340 fully automatic true density meter). Then, calculate the apparent volume V1 of the 30 small circular pieces based on their area, thickness, and number. Porosity = (V1 - V2) / V1 × 100%.

[0212] In this disclosure, the thickness of the negative electrode film layer and the first coating layer can be tested using a thickness tester. During the test, multiple points (such as more than 5) can be taken for testing, and the average value is taken as the test result.

[0213] In this disclosure, the particle size Dn50 of the material can be tested as follows: The negative electrode sheet is obtained by disassembling a secondary battery at 0% SOC. The negative electrode sheet is then subjected to liquid nitrogen embrittlement or ion polishing to prepare a sample. A cross-sectional image of the negative electrode sheet along its thickness direction is obtained using a scanning electron microscope (SEM). The particles to be tested are identified. The SEM image is imported into ImageJ software, and the particles are analyzed using the "Feret diameter" parameter in ImageJ. According to the software manual (ImageJ User Guide IJ 1.46r), the "Feret diameter" parameter represents the maximum spacing between all parallel lines in the two-dimensional projection of the particle, thus characterizing the particle size. The particles obtained in the aforementioned manner are arranged in ascending order of particle size, and a cumulative distribution curve of particle size from smallest to largest is plotted to obtain the Dn50 value. In the cumulative distribution curve of particle size, Dn50 refers to the particle size corresponding to when the cumulative distribution of particle size reaches 50%. To ensure the accuracy of the test results, multiple samples (e.g., 10) can be taken for the above test, and the average value is taken as the final test result.

[0214] In this disclosure, the specific surface area of ​​the materials was measured using a specific surface area analyzer (such as Tristar II 3020M) via nitrogen adsorption and calculated using the BET method. During testing, a fully dried 2g sample is placed in a sample tube and then tested in the specific surface area analyzer. The testing standard can be found in GB / T 19587-2017.

[0215] In this disclosure, material I D / I G All can be tested using the following method: Perform large-area, multi-point Raman mapping scans on the material to obtain the spectrum, and then analyze all the measured I values. D / I G The values ​​are plotted as a statistical distribution histogram. Theoretically, different peaks correspond to different components.

[0216] In this disclosure, a secondary battery in a 0% SOC state means that at 25°C, the secondary battery is discharged at a constant current of 1 / 3C rate to the lower limit cutoff voltage and left to stand for 30 minutes. At this time, the secondary battery is considered to be in a 0% SOC state, that is, in a fully discharged state.

[0217] In this disclosure, both the upper cutoff voltage and the lower cutoff voltage are known in the art, and the voltages recommended in the product specification sheet may be used.

[0218] This disclosure also provides an electrical device that uses a secondary battery as a power source. The electrical device can be, but is not limited to, electronic devices, power tools, electric vehicles, drones, and energy storage devices. Electronic devices can include mobile phones, tablets, laptops, etc.; power tools can include electric drills, chainsaws, etc.; and electric vehicles can include electric cars, electric motorcycles, electric bicycles, etc.

[0219] Example The following embodiments describe the contents of this disclosure in more detail. These embodiments are merely illustrative, as various modifications and variations will be apparent to those skilled in the art within the scope of this disclosure. Unless otherwise stated, all parts, percentages, and ratios reported in the following embodiments are based on mass, and all reagents used in the embodiments are commercially available or synthesized by conventional methods and can be used directly without further processing, and the instruments used in the embodiments are commercially available.

[0220] Performance testing (1) Cyclic performance test The secondary batteries prepared in the following examples and comparative examples were left to stand at 25°C for 60 minutes, and then their cycle performance was tested.

[0221] During testing, the secondary battery was first charged at a constant current of 0.5C to a full charge voltage of 3.65V, and then charged at a constant voltage of 3.65V until the cutoff current of 0.05C. After resting for 5 minutes, it was discharged at a constant current of 0.5C to 2.5V and then rested for 5 minutes. The discharge capacity obtained at this time was taken as the initial capacity.

[0222] Then, a high-rate charge-discharge cycle of 1000 times was performed. The high-rate charge-discharge conditions were as follows: the secondary battery was charged at a constant current of 2C to the full charge voltage of 3.65V, and then continued to be charged at a constant voltage of 3.65V until the cutoff current of 0.02C. After resting for 5 minutes, it was discharged at a constant current of 4C to 2.5V, and then rested for 5 minutes. The discharge capacity after 1000 cycles was recorded. During the cycle, every 100 cycles, a low-rate charge-discharge cycle of 0.5C was performed to eliminate high-current polarization interference. The low-rate charge-discharge conditions were as follows: the secondary battery was charged at a constant current of 0.5C to the full charge voltage of 3.65V, and then continued to be charged at a constant voltage of 3.65V until the cutoff current of 0.05C. After resting for 5 minutes, it was discharged at a constant current of 0.5C to 2.5V, and then rested for 5 minutes.

[0223] The capacity retention rate of a secondary battery after 1000 cycles = (discharge capacity after 1000 cycles / initial capacity) × 100%.

[0224] (2) Ratio performance test The secondary batteries prepared in the following examples and comparative examples were left to stand at 25°C for 60 minutes, and then their rate performance was tested.

[0225] During testing, the secondary battery was first charged at a constant current of 0.5C to a full charge voltage of 3.65V, and then charged at a constant voltage of 3.65V until the cutoff current of 0.05C. After resting for 5 minutes, the secondary battery was discharged sequentially at constant current rates of 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 5C, and 10C to 2.5V. After resting for 5 minutes, the battery was cycled through charge and discharge three times at each rate to obtain the discharge capacity at rates of 0.1C, 0.2C, 0.5C, 1C, 2C, 3C, 5C, and 10C.

[0226] The rate performance of a secondary battery is characterized by the ratio of its discharge capacity at 10C to its discharge capacity at 0.1C. The higher this value, the better the rate performance of the secondary battery.

[0227] Example 1 (1) Preparation of negative electrode sheet Artificial graphite (negative electrode active material), conductive carbon black Super P (negative electrode conductive agent), styrene-butadiene rubber (SBR) (negative electrode binder), and sodium carboxymethyl cellulose (CMC-Na) (negative electrode dispersant) are mixed in a mass ratio of 95:1:2:2, and then deionized water is added as a solvent and stirred evenly to obtain a negative electrode slurry. Hard carbon (first material), conductive carbon black Super P (first conductive agent), styrene-butadiene rubber (SBR) (first binder), and sodium carboxymethyl cellulose (CMC-Na) (first dispersant) are mixed in a mass ratio of 92:2:4:2, and then deionized water is added as a solvent and stirred evenly to obtain a first coating slurry. The negative electrode slurry and the first coating slurry are coated on both surfaces of a copper foil in a single simultaneous coating process, and then dried, cold-pressed, and slit to obtain a negative electrode sheet.

[0228] In the negative electrode sheet, a negative electrode film and a first coating are disposed on both surfaces along the thickness direction of the negative electrode current collector. The boundaries of the two first coatings away from the negative electrode film are staggered along the width direction of the negative electrode current collector. Along the thickness direction of the negative electrode current collector, the orthographic projections of the two first coatings parallel to the length direction of the negative electrode current collector and away from the boundary of the negative electrode film do not coincide. The negative electrode film is formed from negative electrode slurry, and the first coating is formed from first coating slurry.

[0229] In the negative electrode, the particle size Dn50 of the artificial graphite is 15 μm, and the particle size Dn50 of the hard carbon is 10 μm. The electronic conductivity of the negative electrode film at 25°C is 20 S / cm, and the relative friction coefficient between the negative electrode film and the negative electrode current collector is 0.20. The electronic conductivity of the first coating at 25°C is 0.2 S / cm, the relative friction coefficient between the first coating and the negative electrode current collector is 0.15, and the capacity per unit area of ​​the first coating is 3.6 mAh / cm². 2 The width is 2.0mm.

[0230] (2) Preparation of positive electrode sheet Lithium iron phosphate (LiFePO4), polyvinylidene fluoride (PVDF), Super P (Super P), and carbon nanotubes (Carbon Nanotubes) were mixed in a mass ratio of 97:1.5:0.8:0.7. N-methylpyrrolidone (NMP) was then added as a solvent, and the mixture was stirred until homogeneous to obtain a slurry. The slurry was uniformly coated onto both surfaces of an aluminum foil, and after drying, cold pressing, and slitting, the positive electrode sheet was obtained. The unit area capacity of the positive electrode film was 3 mAh / cm². 2 .

[0231] (3) Preparation of the separating membrane A porous polyethylene membrane is used as the base membrane, and an alumina ceramic layer is set on both sides of the base membrane to obtain an isolation membrane.

[0232] (4) Preparation of electrolyte Ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed at a mass ratio of 3:7, and then lithium hexafluorophosphate (LiPF6) was added and mixed thoroughly to obtain the electrolyte. The concentration of LiPF6 was 1 mol / L.

[0233] (5) Preparation of secondary batteries The positive electrode, separator, negative electrode, and separator prepared above are stacked and wound in sequence to obtain an electrode assembly. The positive electrode tab and negative electrode tab are welded on, and then the electrode assembly is put into an aluminum-plastic film packaging bag, electrolyte is injected, and after standing, formation and other processes, a secondary battery is obtained.

[0234] Examples 1-1 to 1-5 Except for the differences shown in Tables 1-1 and 1-2, the preparation process of the secondary battery is the same as that in Example 1.

[0235] The mass percentage of the negative electrode dispersant in the negative electrode slurry remains unchanged. The mass percentage of the first dispersant in the first coating slurry remains unchanged.

[0236] Comparative Examples 1 to 2 Except for the differences shown in Tables 1-1 and 1-2, the preparation process of the secondary battery is the same as that in Example 1.

[0237] The mass percentage of the negative electrode dispersant in the negative electrode slurry remains unchanged. The mass percentage of the first dispersant in the first coating slurry remains unchanged.

[0238] Comparative Example 3 Except for the different composition of the first coating, the preparation process of the secondary battery is the same as that in Example 1.

[0239] The preparation process of the first coating slurry is as follows: alumina ceramic particles, styrene-butadiene rubber (SBR) binder, and sodium carboxymethyl cellulose (CMC-Na) dispersant are mixed in a mass ratio of 94:4:2, and then deionized water is added as a solvent and stirred evenly to obtain the first coating slurry.

[0240] Comparative Example 4 Except for the different composition of the first coating, the preparation process of the secondary battery is the same as that in Example 1.

[0241] The preparation process of the first coating slurry is as follows: conductive carbon black Super P, styrene-butadiene rubber (SBR) binder, and sodium carboxymethyl cellulose (CMC-Na) dispersant are mixed in a mass ratio of 94:4:2, and then deionized water is added as a solvent and stirred evenly to obtain the first coating slurry.

[0242] Comparative Example 5 Except for the absence of a first coating, the preparation process of the secondary battery is the same as that in Example 1.

[0243] Comparative Example 6 Except for the differences shown in Tables 1-1 and 1-2, the preparation process of the secondary battery is the same as that in Example 1.

[0244] The mass percentage of the negative electrode dispersant in the negative electrode slurry remains unchanged. The mass percentage of the first dispersant in the first coating slurry remains unchanged.

[0245] Example 2 Except for the different negative electrode preparation process, the preparation process of the secondary battery is the same as that in Example 1.

[0246] (1) Preparation of negative electrode sheet Artificial graphite (negative electrode active material), conductive carbon black Super P (negative electrode conductive agent), styrene-butadiene rubber (SBR) (negative electrode binder), and sodium carboxymethyl cellulose (CMC-Na) (negative electrode dispersant) are mixed in a mass ratio of 92:2:4:2, and then deionized water is added as a solvent and stirred evenly to obtain a negative electrode slurry. Hard carbon (first material), conductive carbon black Super P (first conductive agent), styrene-butadiene rubber (SBR) (first binder), and sodium carboxymethyl cellulose (CMC-Na) (first dispersant) are mixed in a mass ratio of 88:4:6:2, and then deionized water is added as a solvent and stirred evenly to obtain a first coating slurry. The negative electrode slurry and the first coating slurry are coated on both surfaces of a copper foil in a single simultaneous coating process, and then dried, cold-pressed, and slit to obtain a negative electrode sheet.

[0247] In the negative electrode sheet, a negative electrode film and a first coating are disposed on both surfaces along the thickness direction of the negative electrode current collector. The boundaries of the two first coatings away from the negative electrode film are staggered along the width direction of the negative electrode current collector. Along the thickness direction of the negative electrode current collector, the orthographic projections of the two first coatings parallel to the length direction of the negative electrode current collector and away from the boundary of the negative electrode film do not coincide. The negative electrode film is formed from negative electrode slurry, and the first coating is formed from first coating slurry.

[0248] In the negative electrode, the particle size Dn50 of the artificial graphite is 10 μm, and the particle size Dn50 of the hard carbon is 5 μm. The electronic conductivity of the negative electrode film at 25°C is 20 S / cm, and the relative friction coefficient between the negative electrode film and the negative electrode current collector is 0.05. The electronic conductivity of the first coating at 25°C is 0.2 S / cm, the relative friction coefficient between the first coating and the negative electrode current collector is 0.25, and the capacity per unit area of ​​the first coating is 3.3 mAh / cm². 2 The width is 4.0mm.

[0249] Examples 2-1 to 2-5 Except for the differences shown in Table 2-1, the preparation process of the secondary battery is the same as that in Example 2.

[0250] The mass percentage of the negative electrode dispersant in the negative electrode slurry remains unchanged.

[0251] Table 1-1 Table 1-2 Table 1-3 Table 2-1 Table 2-2 Table 2-3 The test results above show that by including hard carbon in the first material of the first coating, 12.5 ≤ σ e1 / σ e2 ≤250, 10≤σ e1 ≤50 can improve the cycle performance and kinetic performance of secondary batteries.

[0252] In Comparative Examples 1 and 3, the first coating exhibits low electronic conductivity at 25°C, σ e1 / σ e2 >250, the electronic conductivity of the first coating is weak, and there is insufficient electron supply at local sites, which will lead to increased local ohmic polarization, increased DC internal resistance, deterioration of dynamics under high current, and easy occurrence of local metal precipitation during charging. Therefore, the cycle performance and dynamic performance of the secondary battery are not good.

[0253] In Comparative Examples 2 and 4, the first coating exhibits higher electronic conductivity at 25°C, σ e1 / σ e2 <12.5, the first coating has good electronic conductivity and weak electronic blocking effect, which may lead to the concentration of edge current, increasing the risk of short circuit between the positive and negative electrodes. It will also cause an imbalance in electronic and ion conduction of the first coating and increase concentration polarization. Therefore, the cycle performance and kinetic performance of the secondary battery are not good.

[0254] Comparative Example 5 lacks a first coating, making it prone to localized metal deposition during charging, resulting in poor cycle performance and kinetic performance of the secondary battery.

[0255] In Comparative Example 6, the negative electrode film has low electronic conductivity at 25°C, resulting in poor cycle performance and kinetic performance of the secondary battery.

[0256] Example 3 Except for the different negative electrode preparation process, the preparation process of the secondary battery is the same as that in Example 1.

[0257] (1) Preparation of negative electrode sheet Artificial graphite (negative electrode active material), conductive carbon black Super P (negative electrode conductive agent), styrene-butadiene rubber (SBR) (negative electrode binder), and sodium carboxymethyl cellulose (CMC-Na) (negative electrode dispersant) are mixed in a mass ratio of 93:1.5:3.5:2, and then deionized water is added as a solvent and stirred evenly to obtain a negative electrode slurry. Hard carbon (first material), conductive carbon black Super P (first conductive agent), styrene-butadiene rubber (SBR) (first binder), and sodium carboxymethyl cellulose (CMC-Na) (first dispersant) are mixed in a mass ratio of 90.8:3:4.2:2, and then deionized water is added as a solvent and stirred evenly to obtain a first coating slurry. The negative electrode slurry and the first coating slurry are coated on both surfaces of a copper foil in a single simultaneous coating process, and then dried, cold-pressed, and slit to obtain a negative electrode sheet.

[0258] In the negative electrode sheet, a negative electrode film and a first coating are disposed on both surfaces along the thickness direction of the negative electrode current collector. The boundaries of the two first coatings away from the negative electrode film are staggered along the width direction of the negative electrode current collector. Along the thickness direction of the negative electrode current collector, the orthographic projections of the two first coatings parallel to the length direction of the negative electrode current collector and away from the boundary of the negative electrode film do not coincide. The negative electrode film is formed from negative electrode slurry, and the first coating is formed from first coating slurry.

[0259] In the negative electrode, the particle size Dn50 of the artificial graphite is 20 μm, and the particle size Dn50 of the hard carbon is 15 μm. The electronic conductivity of the negative electrode film at 25°C is 20 S / cm, and the relative friction coefficient between the negative electrode film and the negative electrode current collector is 0.10. The electronic conductivity of the first coating at 25°C is 0.32 S / cm, the relative friction coefficient between the first coating and the negative electrode current collector is 0.20, and the capacity per unit area of ​​the first coating is 3.45 mAh / cm². 2 The width is 7.5mm.

[0260] Examples 3-1 to 3-4 Except for the differences shown in Table 3-2, the preparation process of the secondary battery is the same as that in Example 1.

[0261] The relative friction coefficient μ2 between the first coating and the negative electrode current collector is changed by adjusting the surface roughness and surface energy of the copper foil at the corresponding position of the first coating.

[0262] Table 3-1 Table 3-2 Table 3-3 The test results above show that by further adjusting the ratio of the relative friction coefficient μ1 between the negative electrode film and the negative electrode current collector and the relative friction coefficient μ2 between the first coating and the negative electrode current collector, the cycle performance and dynamic performance of the secondary battery can be further improved.

[0263] Examples 4-1 to 4-3 Except for the difference in the unit area capacity of the first coating, the preparation process of the secondary battery is the same as that in Example 1.

[0264] Table 4 The test results above show that by further adjusting the unit area capacity of the first coating, the cycle performance and kinetic performance of the secondary battery can be further improved.

[0265] The above description is merely a specific embodiment of this disclosure, but the scope of protection of this disclosure is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in this disclosure, and these modifications or substitutions should all be covered within the scope of protection of this disclosure. Therefore, the scope of protection of this disclosure should be determined by the scope of the claims.

Claims

1. A secondary battery, comprising an electrode assembly, the electrode assembly including a negative electrode, a positive electrode, and a separator, the separator being located between the negative electrode and the positive electrode, characterized in that, The negative electrode sheet includes a negative current collector, a negative electrode film layer, and a first coating layer. The negative current collector includes a negative electrode body portion and a negative electrode tab extending from one end of the negative electrode body portion. The negative electrode body portion includes a coating area and a transition area. The transition area is disposed between the negative electrode tab and the coating area. The negative electrode film layer is disposed in the coating area. The first coating layer is at least partially disposed in the transition area. The negative electrode film layer includes a negative electrode active material and a negative electrode binder. The negative electrode active material includes graphite. The positive electrode sheet includes a positive current collector and a positive electrode film layer disposed on at least one side of the positive current collector. Along the thickness direction of the positive electrode sheet, the orthographic projection of the first coating layer does not overlap with the orthographic projection of the positive electrode film layer. The first coating comprises a first material and a first binder, the first material comprising hard carbon, and the electronic conductivity of the negative electrode film at 25°C is σ. e1 S / cm, the electronic conductivity of the first coating at 25°C is σ e2 S / cm, the negative electrode plate satisfies: 12.5≤σ e1 / σ e2 ≤250, where 10≤σ e1 ≤50.

2. The secondary battery according to claim 1, characterized in that, 25≤σ e1 / σ e2 ≤150; and / or, 15≤σ e1 ≤30.

3. The secondary battery according to claim 1, characterized in that, 0.1≤σ e2 ≤1.6。 4. The secondary battery according to claim 1, characterized in that, The capacity per unit area of ​​the first coating is Q2mAh / cm². 2 The capacity per unit area of ​​the positive electrode film is Q. p mAh / cm 2 The secondary battery satisfies one or two of the following: (1)1.05≤Q2 / Q p ≤1.30; (2) 10.4≤(σ e1 / s e2 ) / (Q2 / Q p )≤227.3。 5. The secondary battery according to claim 1, characterized in that, The first coating is provided on both surfaces of the negative electrode current collector in the thickness direction, and the negative electrode sheet satisfies at least one of the following: (1) The two first coatings form fusion regions of different widths with the adjacent negative electrode film layers respectively; (2) The boundaries of the two first coatings away from the negative electrode film are staggered from each other along the width direction of the negative electrode current collector; (3) Along the thickness direction of the negative electrode current collector, the orthogonal projections of the two first coatings parallel to the length direction of the negative electrode current collector and far from the boundary of the negative electrode film layer do not coincide.

6. The secondary battery according to claim 1, characterized in that, Based on the total mass of the negative electrode film, the mass percentage of the negative electrode binder is W. 11 , Based on the total mass of the first coating, the mass percentage of the first adhesive is W. 21 , The negative electrode sheet satisfies: (1)1.0≤W 21 / IN 11 ≤2.0; (2)1%≤W 11 ≤4%; (3)4%≤W 21 ≤7%。 7. The secondary battery according to claim 6, characterized in that, The width of the first coating is W t mm, wherein the negative electrode sheet satisfies one of the following: (1)1≤W t <3,1.6≤W 21 / IN 11 ≤2.0; (2)3≤W t <6,1.3≤W 21 / IN 11 ≤1.6; (3)6≤W t ≤9,1.0≤W 21 / IN 11 ≤1.3。 8. The secondary battery according to any one of claims 1-7, characterized in that, The negative electrode film layer includes a negative electrode conductive agent, and based on the total mass of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is W. 12 , The first coating includes a first conductive agent, and the mass percentage of the first conductive agent based on the total mass of the first coating is W. 22 , The negative electrode sheet satisfies: (1)1.0≤W 22 / IN 12 ≤4.0; (2)1%≤W 12 ≤5%; (3)1%≤W 22 ≤5%。 9. The secondary battery according to any one of claims 1-7, characterized in that, The negative electrode sheet satisfies at least one of the following: (1) The relative friction coefficient between the negative electrode film layer and the negative electrode current collector is μ1, the relative friction coefficient between the first coating layer and the negative electrode current collector is μ2, and the negative electrode sheet satisfies: 0.75≤μ2 / μ1≤5, 0.05≤μ1≤0.20, 0.15≤μ2≤0.25; (2) The porosity of the negative electrode film is P1, the porosity of the first coating is P2, and the negative electrode sheet satisfies: 1≤P2 / P1≤2, 20%≤P1≤38%, 32%≤P2≤50%; (3) The thickness of the negative electrode film is H1μm, the thickness of the first coating is H2μm, and the negative electrode sheet satisfies: 0.9≤H1 / H2≤1.

2.

10. The secondary battery according to any one of claims 1-7, characterized in that, The negative electrode sheet satisfies at least one of the following: (1) The specific surface area of ​​the negative electrode active material is 0.8 m². 2 / g to 2m 2 / g; (2) The specific surface area of ​​the first material is 2m². 2 / g to 8m 2 / g; (3) The particle size Dn50 of the negative electrode active material is denoted as D1μm, and the particle size Dn50 of the first material is denoted as D2μm, 0.25≤D2 / D1≤1.5; (4) The particle size Dn50 of the negative electrode active material is denoted as D1μm, and 10≤D1≤20; (5) The particle size Dn50 of the first material is denoted as D2μm, where 5≤D2≤15; (6) The porosity of the first material is 38% to 50%; (7) The first material I D / I G It ranges from 0.8 to 1.4, I D The Raman shift in the Raman spectrum of the first material is 1350±10 cm⁻¹ -1 The intensity of peak D at location, I G The Raman shift in the Raman spectrum of the first material is 1580±10 cm⁻¹ -1 The intensity of the G peak at the location; (8) I of the negative electrode active material D / I G The value ranges from 0.08 to 0.30, I D The Raman shift in the Raman spectrum of the negative electrode active material is 1350±10 cm⁻¹ -1 The intensity of peak D at location, I G The Raman shift in the Raman spectrum of the negative electrode active material is 1580±10 cm⁻¹. -1 The intensity of the G peak at the location.

11. An electrical appliance, characterized in that, Includes the secondary battery as described in any one of claims 1-10.